Tailoring larval diets and sugar sources to enhance development and adult survivorship of Culex quinquefasciatus (Say) (Diptera: Culicidae): Penyesuaian pakan larva dan sumber gula untuk meningkatkan perkembangan dan kelangsungan hidup Culex quinquefasciatus (Say) (Diptera: Culicidae) dewasa - Alfiani, Rahmidevi; Dherika; Zuhri, Ahmad Syafiq; Firdaus, Ainur Subhan; Rachma, Saila; Samiaji, Muhammad Arya Rizqi; Pramurdya, Yesika Nanda; Yusmalinar, Sri; Ahmad, Intan (Perhimpunan Entomologi Indonesia, 2025)
Culex quinquefasciatus (Say) (Diptera: Culicidae) is a primary vector of lymphatic filariasis and various encephalitis viruses, posing significant public health threats. Optimizing mass-rearing protocols for this mosquito species, particularly through improved nutritional strategies, is crucial for enhancing vector control effectiveness and efficiency. This study evaluates the effects of larval diet composition and adult sugar diet on the development and survivability of C. quinquefasciatus. Larvae were fed five diets based on combinations of protein-rich dog food (DF) and carbohydrate-rich rice flour (RF): 100% DF, 100% RF, DF:RF (3:1), DF:RF (1:1), and DF:RF (1:3). Adult mosquitoes were provided with 10% sucrose, 10% dextrose, or 10% honey. Observed parameters included larval and pupal morphometry, pupation time and rate, adult wing length, and adult survival over 50 days. The results showed that the DF:RF (1:1) diet yielded optimal larval length, pupation rate, and adult female wing length, whereas the DF:RF (3:1) diet resulted in the shortest pupation time and largest larval width. The combination of the DF:RF (1:1) diet and honey was the most effective in promoting adult development and survival. These findings provide valuable insights for optimizing mass-rearing protocols, which are essential for research and vector control programs.